PENGARUH REALISASI ANGGARAN, INDEKS PEMBANGUNAN MANUSIA DAN INVESTASI TERHADAP PERTUMBUHAN EKONOMI DI SULAWESI UTARA - Natalia Christina Agnes Rawis; Anderson G. Kumenaung; Jacline I. Sumual (PT. Hasba Edukasi Mandiri, 2025)
Economic growth is one of the key indicators often used to assess a region’s success in implementing development. This study aims to determine the effect of Budget Realization, Human Development Index, and Investment on Economic Growth in North Sulawesi. The data used in this study are secondary data with an observation period of sixteen years, from 2008 to 2023. The analytical method used in this research is multiple linear regression. The software employed for the analysis is EViews 12. The results of the study show that the Budget Realization variable has a negative and insignificant effect on Economic Growth. The Human Development Index variable has a negative and significant effect on Economic Growth, while the Investment variable has a positive and insignificant effect on Economic Growth. Simultaneously, the variables of Budget Realization, Human Development Index, and Investment have a significant effect on Economic Growth in North Sulawesi.